Fortuity in the law of marine insurance - Bennett, Howard (Informa Law, 2007)
This article addresses the meaning and significance of the concept of fortuity within the law of marine insurance. Voluntary conduct, naturally occurring losses and inherent vice, and inevitable losses are analysed, highlighting both the variable role and varied meanings of fortuity and considering the extent to which fortuity represents a presumption as to the interpretation of insurance contracts or an absolute restriction on the scope of insurance.